Effect of Nitrogen and Potassium on In vitro Tuberization of Potato - Zakaria, M; Hossain, MM; Mian, MA Khaleque; Hossain, T; Sultana, N (Plant Tissue Culture and Biotechnology, 2008)
Effects of nitrogen @ 20, 40, 60 and 80 meq in combination with potassium @ 10, 20, 30, 40 and 50 meq on in vitro tuberization of potato were evaluated to find out the optimum concentration of nitrogen and potassium for developing a standard protocol for in vitro tuberization of a popular variety Diamant. Microtuberization was delayed with increasing rate of nitrogen. Number of microtubers were reduced with an increase in total nitrogen but the average weight of microtubers increased with an increase in nitrogen level up to 60 meq. The number and size of microtubers increased with an increase in potassium up to 40 meq. Concentration of nitrogen at 60 meq and potassium at 40 meq in MS medium gave rise to microtubers of large size Key words: In vitro, Tuberization, Potato DOI = 10.3329/ptcb.v17i1.1124 Plant Tissue Cult. & Biotech. 17(1): 79-85, 2007 (June)